Japan and United Nations peacekeeping : new pressures, new responses - Dobson, Hugo, 1971- (Sheffield Centre for Japanese Studies/RoutledgeCurzon series., 2003)
Japan's postwar constitution in which the Japanese government famously renounced war forever has meant that the country has been reluctant, until recently, to commit its armed forces in the international arena. However, in the last decade or so, Japan has played a much more active role in peacekeeping and its troops have been deployed as part of UN forces in trouble spots as varied as the Gulf, Cambodia, the Golan Heights, Kosovo and the East Timor. This book examines these developments within the border context of international relations theory and changes in Japan's domestic and regional pol.